(3eGOI GdMjGI aj YdGeGJ LejY GdCTjGA GdeSeheI ef GdeWGYe hGdeTGQH hUag YdGL Pdc hJQjGbGJg ef eVGQI hajg fYJ GdCMLGQ hefGaYgGs - (3eMeO Hf CHj HcQ Hf eMeO Hf MSf Hf Ydj GdaGQSj , HOQ GdOjf CHh YHO Gddg,J (B677 (3g` s ((3eMeO GdWfOJGfi s)
(3ChdgG (B:s
(3Ef Chd eG jfHZi Cf jbOe ai UOQ cd cJGH CeG HYO abO Yde NGUI GdfGS hcKjQ ef gGeJge s
(3BNQgG (B:s
(3hGdfGS CMb HEJNGPgG , hCMbge HPdc Gdedhc hGdYXeGA JeJ s
(3fSNI KGfjI NRGFfjIs
(3ePgHI GdWGdY hGdYfGhjfs
(3cJH YdjgG CfgG ef JCdja eMeO GdNWjH GdbRhjfi ? ddebQ GdCTQa CHj GdeMGSf jhSa fGXQ GdLjTs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B55 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B9 - (3U (B117s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA GdWH (B- (3bSe GdcJGH GdChd (B- (3U (B163 ; (3cTa GdXfhf dMGLi NdjaI(B: (3L (B2 - (3U (B1574s
Keywords: (3GdWHs